Novel Susah Sinyal Karya Ika Natassa dan Ernest Prakasa: Kajian Stilistika - Rohman, M Fatkhur; Matildis Banda, Maria; Weda Kusuma, I Nyoman (Stilistika : Journal of Indonesian Language and Literature; Vol 1 No 2 (2022): Volume 1 No. 2. April 2022, 2022)
This study aims to determine the description of the structure (plot, setting, character) and style of language, namely the novel "Hard Signal" by Ika Natasya and Ernest Prakasa published by PT Gramedia Pustaka Utama, Jakarta, the first edition of 2018 and the book thickness is 272 pages. This type of research is descriptive qualitative research using reading, listening and note-taking techniques. The research procedures include: (1) Understanding the structure and types of language styles, then reading and studying the novel, Difficult Signals, (2) Recording data in the form of novel structures and language styles, (3) Classifying the data that has been obtained, (4) Describing the structure and language style obtained, (5) Concluding the results of the analysis.             The result of this research is the structure contained in the novel of Difficult Signal by Ika Natasya and Ernest Prakasa, namely: The plot used in this novel is a mixed plot but uses more advanced plots. Setting, this novel takes several settings as a story but focuses more on the Sumba setting. In character, the main character in this novel is Ellen, a mother who is firm, independent, and hardworking. Kiara, a high school girl who is growing up is spoiled, kind, and loving. Grandma, a grandmother who loves family, is kind, and also wise. Iwan, a friend and work partner of Ellen who is humorous, and kind, Saodah and Ngatno, workers and housemaids who are humorous, Yos and Melki, a travel and hotel officer who has a humorous and kind character. Abe, one of the hoteliers who is firm, wise, kind, and friendly. Aunt Maya, a hotel owner who is humorous, kind and also compassionate. Next, the language style in the novel, Difficult Signal. The results of this study found that there were 102 uses of language styles in total, from 16 types of language styles, and in 4 classifications.